2002
DOI: 10.1074/jbc.m109760200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Mitochondrial Death Pathway in Chemopreventive Benzyl Isothiocyanate-induced Apoptosis

Abstract: In the present study, we studied the molecular mechanism underlying cell death induced by a cancer chemoprotective compound benzyl isothiocyanate (BITC). The cytotoxic effect of BITC was examined in rat liver epithelial RL34 cells. Apoptosis was induced when the cells were treated with 20 M BITC, characterized by the appearance of phosphatidylserine on the outer surface of the plasma membrane and caspase-3 activation, whereas no caspase activation and propidium iodide incorporation into cell were detected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 45 publications
8
150
0
1
Order By: Relevance
“…5 M (PEITC) [93] 10 M (PEITC) [94] 5 M (SFN) [90] 15 M (SFN) [91] 5 M (BITC) [43] 10 M (PEITC) [95] Induction of Appears to require higher concentrations 25 M (PEITC/BITC) A c c e p t e d M a n u s c r i p t necrosis than induction of apoptosis [96] 50 m (BITC) [97] Metastasis ITCs inhibit cell adhesion, invasion and migration in vitro, and metastasis in vivo 5 M (AITC) [98] 5 M (PEITC) [99] 2 M (PEITC) [24] 2 g/ml (SFN) [100] Inhibition of angiogenesis ITCs inhibit angiogenesis in in vitro and in vivo models 1 M (PEITC) [24] 5 g/ml (AITC) [27] 0.1 -1 M (SFN) [23] Page 30 of 38…”
Section: Discussionmentioning
confidence: 99%
“…5 M (PEITC) [93] 10 M (PEITC) [94] 5 M (SFN) [90] 15 M (SFN) [91] 5 M (BITC) [43] 10 M (PEITC) [95] Induction of Appears to require higher concentrations 25 M (PEITC/BITC) A c c e p t e d M a n u s c r i p t necrosis than induction of apoptosis [96] 50 m (BITC) [97] Metastasis ITCs inhibit cell adhesion, invasion and migration in vitro, and metastasis in vivo 5 M (AITC) [98] 5 M (PEITC) [99] 2 M (PEITC) [24] 2 g/ml (SFN) [100] Inhibition of angiogenesis ITCs inhibit angiogenesis in in vitro and in vivo models 1 M (PEITC) [24] 5 g/ml (AITC) [27] 0.1 -1 M (SFN) [23] Page 30 of 38…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the decrease of mitochondrial membrane potential and increase of cytochrome c release may be due to the alteration in the mitochondria structure. In addition, the mitochondrial swelling and disruption have also been reported in various types of tumor cells exposed to other putative cancer chemopreventive agents during apoptosis (32,33), suggesting that the change of mitochondrial function and structure observed during curcumin-induced apoptosis in A549 cells was perhaps not an agent-or cell type-specific phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that curcumin induced loss of mitochondrial membrane potential in a dose-dependent manner. In addition, the loss of MMP has also been reported in various types of tumor cells exposed to other putative cancer chemopreventive agents during apoptosis (19,20). These would suggest that the change of mitochondrial function observed during curcumin-induced apoptosis in A549 cells was perhaps not an agent-or cell type-specific phenomenon.…”
Section: Discussionmentioning
confidence: 99%